The Development of Structured Inquiry with three-Level Representation Module - Hidayati - Hidayati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
Mole concepts are essential parts of chemistry learning and have become preliminaries to learn other chemistry concepts. However, the learning resource used has not incorporated three representations, resulting in students' learning outcomes. This study aimed to develop a structured inquiry module in terms of validity and practicality. The method used in this study is research development through the use of the Plomp model. There were 141 senior high school students in Padang participating in the study. The instruments of this study included cognitive tests. The result of the study indicated that the structured inquiry module had high validity (V=0.98), practicality based on teachers' response (P=0.36) and students' response (P=0.36)Furthermore, the result of the t-test toward hypotheses of the learning outcome of the mole concept showed that the learning outcome of the mole concept in experimental groups was higher than that of control groups at both schools. Hence, the structured inquiry module has high validity and practicality. It is also effective to be used in chemistry learning at school. The module developed is a module with three levels of representation (macroscopic level, submicroscopic level and symbolic level). The module contains structured inquiry activities. The module also includes several components such as teacher guidelines, student activity sheets, worksheets, worksheet keys, test sheets, test sheet keys..